Monocyte/macrophage-mediated venous thrombus resolution - Lu, Meng-Jiao; Zhang, Jia-Qi; Nie, Zhou-Yu; Yan, Tian-Hua; Cao, Yong-Bing; Zhang, Li-Chao; Li, Ling (Frontiers in Immunology, 2024)
Venous thromboembolism (VTE) possesses a notable risk of morbidity and mortality. The natural resolution of venous thrombus might be as a potential alternative treatment strategy for VTE. Monocytes/macrophages merge as pivotal cell types in the gradual resolution of thrombus. In this review, the vital role of macrophages in inducing inflammatory response, augmenting neovascularization and facilitating the degradation of fibrin and collagen during thrombus resolution was described. The two phenotypes of macrophage involved in thrombus resolution, and their dual functions were discussed.Macrophages expressing various factors, including cytokines and their receptors, adhesion molecule, chemokine receptor, vascular endothelial growth factor receptor, pro-fibrinolytic or anti-fibrinolytic related enzymes and other elements, are explored for their potential to promote or attenuate thrombus resolution. Furthermore, the review provides a comprehensive summary of new and promising therapeutic candidate drugs associated with monocytes/macrophages have been demonstrated to promote or impair thrombus resolution. However, further clinical trials are essential to validate their efficacy in VTE therapy.